Diagnosis Keterampilan Penggunaan Teknologi dalam Belajar Siswa di SMP N 19 Palembang - Nadya Ramadinah; Ghina Rizki Amalia; Juwita Madira; Silvia AR; Resti Okta Sari (JISPENDIORA Jurnal Ilmu Sosial Pendidikan Dan Humaniora, 2025)
Technology has brought about significant changes in the educational landscape, particularly in the way students access and analyze data. Determining how well seventh grade students at SMP Negeri 19 Palembang use technology as a learning aid was the aim of this study. Students were given questionnaires to complete and observations were made using quantitative approaches. 48.42% of pupils had strong technology use skills, according to the data, while none of the kids fell into the low category. Despite the fact that the majority of students are used to using digital devices and online learning platforms, these findings show that they still need to enhance their digital literacy in order to use technology more responsibly and efficiently. This study demonstrates how crucial the school environment, instructors, and counselors are in offering continuous assistance on digital literacy. Furthermore, to improve the efficiency of technology utilization in the educational process, systematic training is required. The technology acceptance model (TAM) focuses on how technology might facilitate learning and how easy it is to use in order to understand students' adoption of it.